Integrated information service for plug-in electric vehicle users including smart grid functions - Csonka, Bálint; Csiszár, Csaba (Transport, 2019)
Information provision can mitigate the drawbacks of electric vehicle use. In this paper, we elaborate an integrated Information Service (IS) for Plug-in Electric Vehicle (PEV) users that cover each process of use. The system elements and their relations are modelled. We deduce the functions from the negatives of electric vehicles compared to conventional ones. The information management processes are elaborated in detail. We focus on the charging and recharging periods considering dynamic electricity rates in the Smart Grid in order to minimalize the cost of charging from the user’s perspective.  We elaborate a cost saving method and evaluate the effects of dynamic tariff and forethoughtful behaviour. Since our proposed information, service covers each phase of use and reduces charging costs the presented solution simplifies electric vehicle use and improves efficiency. Furthermore, we elaborate the automatic charging scheduling methods that significantly reduce the charging cost and the fluctuation of the electricity demand.